Conserved cysteines in the finger domain of the epithelial Na(+) channel α and γ subunits are proximal to the dynamic finger–thumb domain interface - Blobner, Brandon M. (J Biol Chem, 2018)
The epithelial Na(+) channel (ENaC) is a member of the ENaC/degenerin family of ion channels. In the structure of a related family member, the “thumb” domain's base interacts with the pore, and its tip interacts with the divergent “finger” domain. Between the base and tip, the thumb domain is characterized by a conserved five-rung disulfide ladder holding together two anti-parallel α helices. The ENaC α and γ subunits' finger domains harbor autoinhibitory tracts that can be proteolytically liberated to activate the channel and also host an ENaC-specific pair of cysteines. Using a crosslinking approach, we show that one of the finger domain cysteines in the α subunit (αCys-263) and both of the finger domain cysteines in the γ subunit (γCys-213 and γCys-220) lie near the dynamic finger–thumb domain interface. Our data suggest that the αCys-256/αCys-263 pair is not disulfide-bonded. In contrast, we found that the γCys-213/γCys-220 pair is disulfide-bonded. Our data also suggest that the γ subunit lacks the terminal rung in the thumb domain disulfide ladder, suggesting asymmetry between the subunits. We also observed functional asymmetry between the α and γ subunit finger–thumb domain interfaces; crosslinks bridging the α subunit finger–thumb interface only inhibited ENaC currents, whereas crosslinks bridging the γ subunit finger–thumb interface activated or inhibited currents dependent on the length of the crosslinker. Our data suggest that reactive cysteines lie at the dynamic finger–thumb interfaces of the α and γ subunits and may play a yet undefined role in channel regulation.